Business Analysis and Recommendation For Telkomsel Sub-Branch Offices in Designing Outlet Loyalty Programs - Imandaru, Yudhawijaya; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2013)
Mobile telecommunications industry In Indonesia has experienced rapid growth. Ever since the implementation of PERMENKOINFONo.1/2010 which concerns liberalization of telecommunications In Indonesia, there are number of mobile telco operators that being acquired by foreign investors. Based on the reports of the Indonesian Cellular Telecommunications Association (ATSI), estimated the total number of mobile phone subscribers at the end of 2011 has reached 240 million users in which the number of GSM prepaid subscribers dominates with more than 95%. Full implementation of hard cluster system by Telkomsel is considered as a threat for outlets due to cross-cluster restrictions as that would limit its sales area. Another concern for Telkomsel sales partners, including authorized dealers, is cooperation between Telkomsel with retail companies to increase distribution and sales through media ATM and non-ATM. Moreover, restrictions on cross-cluster rules do not applied to transactions via ATM, non-ATM and retail. Analysis tools that being used are PESTEL, Porterâ€™s 5 Forces and Resource Based View which than combined to arrange SWOT analysis. Result of analysis identifying root causes which being derived into 4 areas, namely distribution, marketing, regulation, and price competition. In order to improve the performance of Telkomsel sub-branches in sales functions and market domination in sub-branches area therefore Telkomsel should focus its strategy in distribution and marketing area. This research would give a business solution for Telkomsel in form of framework in designing loyalty programs for outlets. Expected results from its implementation are increase sales performance, market shares domination, and high outlet loyalty.Â Key Words: Hard Cluster, outlet Loyalty, increase sales performance